The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000354112
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in Patients with Idiopathic Pulmonary Fibrosis - A Review

Abstract: Among the various types of interstitial lung diseases, idiopathic pulmonary fibrosis (IPF) is the most common disorder and has a poor prognosis and a limited response to pharmacological treatment. In patients with IPF, functional exercise tolerance and quality of life have been shown to be significantly decreased. Current IPF guidelines suggest only a weak recommendation for pulmonary rehabilitation (PR). However, PR is regarded as a reasonable choice for the majority of patients with IPF. This review will sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 54 publications
2
55
0
9
Order By: Relevance
“…Exercise training and rehabilitation programmes in patients with chronic respiratory disease have been reported to improve symptoms and exercise capacity, but the extent and duration of the effect in specific settings need to be fully clarified [85,86]. Although the majority of data derive from studies performed in COPD subjects [87], in recent years, pulmonary rehabilitation programmes have been adopted for patients with ILDs and particularly in IPF [88,89]. The introduction of new drugs aimed to slow the progression of the disease in IPF patients will further increase the number of patients that, in the near future, will be suitable for and benefit from such programmes.…”
Section: Exercise Training and Pulmonary Rehabilitation In Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise training and rehabilitation programmes in patients with chronic respiratory disease have been reported to improve symptoms and exercise capacity, but the extent and duration of the effect in specific settings need to be fully clarified [85,86]. Although the majority of data derive from studies performed in COPD subjects [87], in recent years, pulmonary rehabilitation programmes have been adopted for patients with ILDs and particularly in IPF [88,89]. The introduction of new drugs aimed to slow the progression of the disease in IPF patients will further increase the number of patients that, in the near future, will be suitable for and benefit from such programmes.…”
Section: Exercise Training and Pulmonary Rehabilitation In Ildmentioning
confidence: 99%
“…The introduction of new drugs aimed to slow the progression of the disease in IPF patients will further increase the number of patients that, in the near future, will be suitable for and benefit from such programmes. Rehabilitation programmes in IPF patients have been shown to be safe and effective on exercise capacity, quality of life and dyspnoea [88,90,91]. An ongoing two-arm double-blind multicentre randomised placebo-controlled trial (HOPE-IPF study) to determine the effect of breathing a hyperoxic gas mixture with either a constant oxygen fraction of 60% or as-required oxygen up to 40% to maintain a saturation of ⩾88% in 88 patients with IPF treated with nintedanib, along 8 weeks of aerobic cycle exercise training undertaken three times weekly [92].…”
Section: Exercise Training and Pulmonary Rehabilitation In Ildmentioning
confidence: 99%
“…Exercise training (ET) is a major component in these programs, since significant improvements have been reported in exercise and functional capacities, level of dyspnea and QOL among COPD patients [7,8,9]. As stated, exercise tolerance and QOL are severely impaired in IPF, thus rehabilitative ET may be valuable in order to maintain function in daily living activity [9,10]. The few randomized controlled studies that have been conducted with IPF patients showed an improvement in 6-min walking distance (6MWD), dyspnea and QOL following ET interventions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The few randomized controlled studies that have been conducted with IPF patients showed an improvement in 6-min walking distance (6MWD), dyspnea and QOL following ET interventions [11,12]. Despite these encouraging results, extensive research is lacking with respect to ET on clinical outcomes in IPF, and the level of recommendation for this exercise treatment is weak at present [2,10]. The aim of this randomized controlled study was to examine the effect of an ET-based pulmonary rehabilitation program on exercise tolerance, functional capacity, pulmonary function, dyspnea and QOL in patients with IPF.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, patients with chronic respiratory disease other than COPD also suffer from daily symptoms, muscle weakness, exercise intolerance, impaired mood status, poor quality of life and physical inactivity, despite optimal medical treatment [100][101][102][103][104][105][106]. Most of the new studies confirm the positive effects of exercise-based pulmonary rehabilitation in patients with nonsmall cell lung cancer (pre-/post-lung resection) [107][108][109][110][111][112][113][114][115][116][117], chronic respiratory failure due to kyphoscoliosis [118], pre-/post-lung transplantation [119][120][121][122], cystic fibrosis [123], bronchiectasis [124], severe respiratory failure receiving extracorporeal membrane oxygenation [125,126], interstitial lung disease [6,[127][128][129], and pulmonary arterial hypertension [130][131][132]. Existing COPD pulmonary rehabilitation programmes can be adapted to the particular needs of patients with chronic respiratory disease other than COPD, in particular the non-exercising parts [30].…”
Section: Pulmonary Rehabilitation In Chronic Respiratory Disease Othementioning
confidence: 99%